Managing credit risk and improving access to finance in green energy projects - Purkayastha Dhruba (Asian Development Bank Institute (ADBI), 2018)
The cost of finance has a relatively high impact on the returns and viability of clean energy projects compared with fossil fuel-based energy projects, because the operating costs for renewable energy projects are very low. Credit risk assessment and ratings, which have usually been an inappropriate measure of credit risk for clean energy finance, have a significant influence on the cost of finance. Factors like inadequate credit information, a lack of historical data at the project level, and the higher risk of technological obsolescence lead to credit market failure in clean energy finance, leading to mispricing of risk and poor capital allocation to clean energy infrastructure in the economy. Access to institutional finance is more constrained in the distributed renewable energy sector, as the transaction costs are high, consumer credit risk is high or unknown, and a variety of other challenges exist. It is important to ease these constraints, through appropriate policy and financing interventions to crowd in domestic banks, by improving the quality of credit information, both technical and commercial, creating suitable financial intermediaries, and providing risk mitigation solutions.
Keywords: Q5; Q56; 330; corporate finance; financial risk; financing; ratings and rating agencies; renewable energy